2020
DOI: 10.1016/j.isci.2020.101373
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Oncology: New Insights into an Ancient Disease

Abstract: Summary Cancer has deep evolutionary roots and is an important source of selective pressure in organismal evolution. Yet, we find a great deal of variation in cancer vulnerabilities across the tree of life. Comparative oncology offers insights into why some species vary in their susceptibility to cancer and the mechanisms responsible for the diversity of cancer defenses. Here we provide an overview for why cancer persists across the tree of life. We then summarize current data on cancer in mammals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 109 publications
(150 reference statements)
0
30
0
Order By: Relevance
“…Accordingly, we should expect a higher probability of developing cancer in larger and longer-lived organisms than smaller ones, although this does not occur [6][7][8][9][10] . Several hypotheses have been proposed to explain the different evolutionary strategies that have arisen to fight cancer [11] , including specific adaptations to the environment, fitness, DNA damage responses, tissue microenvironments, and cellular senescence [12,13] . Recently, the availability of the genomes of a wide variety of species has prompted the search for genes that could explain the differences arising in cancer incidence between species [14] .…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, we should expect a higher probability of developing cancer in larger and longer-lived organisms than smaller ones, although this does not occur [6][7][8][9][10] . Several hypotheses have been proposed to explain the different evolutionary strategies that have arisen to fight cancer [11] , including specific adaptations to the environment, fitness, DNA damage responses, tissue microenvironments, and cellular senescence [12,13] . Recently, the availability of the genomes of a wide variety of species has prompted the search for genes that could explain the differences arising in cancer incidence between species [14] .…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of converging associations between prokaryotic microorganisms, particularly bacteria, and the incidence of cancer in the animal kingdom, including humans [69,70]. Similar to the case of infectious diseases, written records from different cultures [71][72][73][74] and paleo-oncology/pathology data [75][76][77][78] clearly show that cancer is indeed an ancient disease ( Table 2).…”
Section: Bacteria and Cancermentioning
confidence: 96%
“…This is mainly due to multiple functions attributed to GOLPH3 (Sechi et al, 2015), including, the sorting of Golgi glycosyltransferases (Ali et al, 2012; Isaji et al, 2014; Pereira et al, 2014), the modulation of focal adhesion dynamics (Arriagada et al, 2019), induction of membrane curvature (Rahajeng et al, 2019), and an intriguing function for a Golgi protein, regulating mitochondrial function (Nakashima-Kamimura et al, 2005). Because cancer has deep evolutionary roots that arise as a consequence of the multicellularity (Boddy et al, 2020), and is widespread across animals (Albuquerque et al, 2018), studying the evolution of the GOLPH3 gene family in non-model species can provide significant information for a comparative oncology approach, which is emerging as an integrative field to tackle cancer (Boddy et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Today, the GOLPH3 gene family is viewed as a group of genes containing two paralogs (GOLPH3 and GOLPH3L) with 1:1 orthologs among most vertebrate species (Wu et al, 2000; Bell et al, 2001). Among amniotes, it is suggested that birds are less susceptible to cancer in contrast to mammals (Ratcliffe, 1933; Lombard and Witte, 1959; Effron et al, 1977; Pang et al, 2012; Møller et al, 2017; Boddy et al, 2020); although this information should be taken with caution given sampling bias (Hochberg and Noble, 2017). Thus, the study of genes associated with cancer in birds could provide clues about the genetic bases associated with this difference and suggest additional model systems that could help to understand the biology of the GOLPH3 gene family.…”
Section: Introductionmentioning
confidence: 99%